Improvement with Infliximab of a Disseminated Sarcoidosis in a Patient with Crohn's Disease. (6th February 2014) - Chebib, Nader; Piégay, Fabrice; Traclet, Julie; Mion, François; Mornex, Jean-François
Abstract : Sarcoidosis and Crohn's disease are systemic granulomatous disorders affecting the lung and the intestine, respectively, with variable involvement of other organs and are seldom associated. While anti-TNF α is a recognized treatment of Crohn's disease, its usage is discussed in sarcoidosis. A 42-year-old man presented with an 11-year-long history of Crohn's disease; upon discovery of an abnormal chest CT scan the diagnosis of multivisceral sarcoidosis was made and, later, a treatment with an anti-TNF α agent, infliximab, was started, because of worsening Crohn's disease recurrences. CT scan demonstrated net regression of pulmonary opacities and hepatosplenic lesions. Pathologies obtained from the intestinal tract and the bronchi of the patient were, respectively, characteristic of Crohn's disease and sarcoidosis leading to the diagnosis of both diseases. We report a rare case of steroid resistant Crohn's disease associated with multivisceral sarcoidosis, treated successfully by an anti-TNF α agent, infliximab.